Are energy performance certificates a strong predictor of actualenergy use? Evidence from high-frequency thermostat panel data - Tensay Hadush Meles; Niall Farrell; John A. Curtis (The Economic and Social Research Institute (ESRI), 2023)
This paper evaluates the extent with which Energy Performance Certificates (EPCs) reflect observed energy used for heating. We use high-frequency smart thermostat panel data in combination with building characteristics and hourly weather information. We exploit variations in boiler operation in the neighborhood of a steady state indoor temperature to elicit the predictive power of an EPC rating on energy use for heating. We find that the implied energy saving of upgrading from the lowest to highest EPC category is more than 3.5 times greater than that identified through ex-post analysis; boiler time operation is 52% greater among the lowest EPC-rated properties relative to the highest, while the EPC rating itself suggest a 183% difference in energy requirements. The findings cast doubt on the efficacy of public energy efficiency retrofit targets aligned to specific EPC standards.
Keywords: 330; Building energy performance certificates; Smart thermostat; Exante energy use; Ex-post evaluations; Energy efficiency; Climate change